Impact of Covid-19 on Infrastructure Sector in India - Meena, Ms. Deepti; Meena, Mr. G.R. (The journal of contemporary issues in business and government, 2022)
In June 2020, COVID-19 cases increased, making India the third-worst affected nation globally. However, the lockdown had a considerable effect on the infrastructure sector's output, including but not limited to the transportation, power, and construction subsectors. Although there are several causes for this, the lack of human capital made it more difficult. This paper aims to evaluate the fundamental situation in India and discuss possible impact on the infrastructure sector.